DESKRIPSI PENGADAAN BARANG ATAU JASA BERBASIS E-PROCUREMENT DI PT. PLN (PERSERO) AREA KEDIRI - Fitri Ayuningtias (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The research aims to describe the procurement process of goods and services based on e-procurement procedure in PT. PLN (Persero) around Kediri. Such an online service is implemented to give convenience for the users, especially on the information transparency, procedure, and cost and to increase the rate control of the society, government, and other relevant parties. Another benefit is to establish selective logging system, auction, competitive bidding price, and trusted goods or service quality. Those advantages can increase public confidence to the service provided by PT. PLN (Persero) and reduce fraud. This descriptive qualitative research applies a case study approach in which the data are obtained through observation, interview, document study, and literature review. The result of the analysis shows that e-procurement has run very well in the Persero of Kediri area and is in accordance with the procedure. PT. PLN of Kediri is able to carry out the principles of good corporate governance, accountabillity, but not on the aspect of transparency.Keyword : Evaluation, Procurement of goods and services, conventional, E-procurement